Carbon fiber: Characterization and evaluation of the inflammatory response and toxicity in rats - Maciel, Clarissa Carvalho Martins [UNESP]; Torquato, Letícia Cavassini [UNESP]; Chelin Suárez, Eduardo Antonio [UNESP]; Pereira, Kauê Alberto [UNESP]; Jardini, Maria Aparecida Neves [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP]; Marcuzzo, Jossano Saldanha; De Marco, Andrea Carvalho [UNESP] (Wiley, 2023)
This study aimed to evaluate the Carbon Fiber obtained from PAN textile and cotton fiber in their different forms of presentation: non-activated carbon fiber felt (NACFF), activated carbon fiber felt (ACFF), silver activated carbon fiber felt (Ag-ACFF), and activated carbon fiber tissue (ACFT), to obtain scaffolds as a potential material with properties related to the synthetic bone graft. Characterization tests performed: surface wettability, traction, swelling, and in vivo tests: evaluation of the inflammatory response by implanting the materials in the subcutaneous tissue of 14 Wistar rats, evaluation of collagen fibers by picrosirius red staining and assessment of toxicity in the following organs: heart, spleen, liver, and kidney. In the wettability test, NACFF and ACFT were hydrophobic (θ124° and 114°), ACFF and Ag-ACFF were hydrophilic. For maximum stress, ACFF was more resistant (2.983 ± 1.059) p <.05. In the swelling test, the Ag-ACFF and ACFF groups showed the highest absorption percentage for the PBS solution and distilled water (p <.001). The organs showed no signs of acute systemic toxicity. The implant regions showed mild to moderate inflammatory infiltrate at 7 and 21 days. Only the ACFT group did not show the maturation of type I collagen fibers in 21 days. Through the conducted analyses, the ACFT shows little potential to be indicated as a possible scaffold. Therefore NACFF, ACFF, and Ag-ACFF have the potential to be considered scaffolds due to the following characteristics presented: good absorption rate, hydrophilicity, and non-toxic.
Keywords: biocompatible materials; bone regeneration; carbon fiber; scaffolds; tissue engineering